2019
DOI: 10.3390/s19235089
|View full text |Cite
|
Sign up to set email alerts
|

Soft Magnetic Amorphous Microwires for Stress and Temperature Sensory Applications

Abstract: Amorphous ferromagnetic materials in the form of microwires are of interest for the development of various sensors. This paper analyzes and argues for the use of microwires of two basic compositions of Co71Fe5B11Si10Cr3 and Fe3.9(4.9)Co64.82B10.2Si12Cr9(8)Mo0.08 as stress/strain and temperature sensors, respectively. The following properties make them suitable for innovative applications: miniature dimensions, small coercivity, low anisotropy and magnetostriction, tunable magnetic structure, magnetic anisotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 76 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…The amorphous microwires of Co 70 Fe 4 B 13 Si 11 Cr 2 alloy with near-zero magnetostriction [ 37 , 38 ] produced by Tailor-Ulitovsky technique [ 39 ] with different metal cross-section dimensions from 6.4 to 28 µm (6.4, 8, 8.5, 10, 22 and 28 µm) were investigated. The glass shell had the thicknesses of 2.5, 2.8, 2, 2.3, 1, and 3 µm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The amorphous microwires of Co 70 Fe 4 B 13 Si 11 Cr 2 alloy with near-zero magnetostriction [ 37 , 38 ] produced by Tailor-Ulitovsky technique [ 39 ] with different metal cross-section dimensions from 6.4 to 28 µm (6.4, 8, 8.5, 10, 22 and 28 µm) were investigated. The glass shell had the thicknesses of 2.5, 2.8, 2, 2.3, 1, and 3 µm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Many efforts have been made to obtain RE-Co particles with controllable magnetic properties by physical and chemical methods. , Pr doping in SmCo 5 is expected to obtain optimal magnetic performance, while the difficulty lies in controlling the composition homogeneity in multicomponent rare earth particles. Relative to physical methods, chemical methods are conducive to regulating particle size and morphology, which have a considerable impact on magnetic properties. However, the preparation of RE-based particles by direct solution-based chemical synthesis is blindingly challenging because of the antioxidant chemical instability of RE.…”
Section: Introductionmentioning
confidence: 99%
“…This difference in the stress state not only affects the magnetization reversal process and the shape of a hysteresis loop [7,8] but it should also affect the processes of crystal formation at the initial stages. Previously, the effect of mechanical stresses on the crystallization and magnetic properties of Co-rich microwires was observed in [9][10][11]. It was found that isothermal annealing led to the formation of crystallites with an elongated shape, and there existed a preferential orientation along the microwire axis [12].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the growth of crystals oriented along the microwire axis led to a giant increase in the coercivity (by an order of magnitude or more). Moreover, the cumulative effects of stresses on the crystallization and high-frequency properties of microwires was demonstrated in [11].…”
Section: Introductionmentioning
confidence: 99%